Determination of Formation Conditions of Camliktepe (Milas-mugla) Zultanites by Fluid Inclusion Studies - Akhundlu, Azar; Kalender, Leyla; Kara, Hatice (Maik Nauka/Interperiodica/Springer, 2024)
The bauxite occurrences are associated with Triassic quartz meta-limestones and Jura platform type limestones in Kozagac-Camliktepe (Mugla-Milas). The formation of bauxites is related to the acceleration of the decomposition process of waters with different chemical compositions due to regional climatic conditions. Diaspore is a type of bauxite mineral. Zultanite is a color-changing gemstone and is a diaspore. The homogenisation temperature results show that the zultanite homogenisation temperature varies from 191 to 350 degrees C. The salinity of zultanites varies from low to high (2.1 wt % to 7.5 wt % NaCl eq.). T-h CO2 values are range from 26 to 35.7 degrees C, and the T-m CO2 values range from -58 to -64 degrees C. These data show that the gas compositions are not pure carbon dioxide. The high CO2 content of fluid inclusions in the studied zultanite indicates that the zultanite formation is at high-temperature medium-pressure conditions due to retrograde metamorphism of carbonate platforms. The low CO2 content demonstrates that the zultanite might have occurred after the weathering wasprocess.
Keywords: diaspore; zultanite; fluid inclusion; Turkey (Mugla)